Enzymatic activity of poliovirus RNA polymerase mutants with single amino acid changes in the conserved YGDD amino acid motif. - Jablonski, S A (1991)
RNA-dependent RNA polymerases contain a highly conserved region of amino acids with a core segment composed of the amino acids YGDD which have been hypothesized to be at or near the catalytic active site of the molecule. Six mutations in this conserved YGDD region of the poliovirus RNA-dependent RNA polymerase were made by using oligonucleotide site-directed DNA mutagenesis of the poliovirus cDNA to substitute A, C, M, P, S, or V for the amino acid G. The mutant polymerase genes were expressed in Escherichia coli, and the purified RNA polymerases were tested for in vitro enzyme activity. Two of the mutant RNA polymerases (those in which the glycine residue was replaced with alanine or serine) exhibited in vitro enzymatic activity ranging from 5 to 20% of wild-type activity, while the remaining mutant RNA polymerases were inactive. Alterations in the in vitro reaction conditions by modification of temperature, metal ion concentration, or pH resulted in no significant differences in the activities of the mutant RNA polymerases relative to that of the wild-type enzyme. An antipeptide antibody directed against the wild-type core amino acid segment containing the YGDD region of the poliovirus polymerase reacted with the wild-type recombinant RNA polymerase and to a limited extent with the two enzymatically active mutant polymerases; the antipeptide antibody did not react with the mutant RNA polymerases which did not have in vitro enzyme activity. These results are discussed in the context of secondary-structure predictions for the core segment containing the conserved YGDD amino acids in the poliovirus RNA polymerase.